Chemical profiling of Justicia vahlii Roth. (Acanthaceae) using UPLC-QTOF-MS and GC-MS analysis and evaluation of acute oral toxicity, antineuropathic and antioxidant activities. (6th April 2022) - Basit, Abdul; Ahmad, Saeed; Khan, Kashif ur Rehman; Naeem, Abid; Usman, Muhammad; Ahmed, Imtiaz; Shahzad, Muhammad Nadeem
Abstract: Ethnopharmacological relevance: Justicia vahlii Roth. (Acanthaceae), also called as kodasoori and bhekkar is an annual therophyte erect or decumbent herb used traditionally in toothache, skin diseases (itching, topical inflammation) and for the treatment of various respiratory disorders. Aim of the study: The current study aimed at exploring pain cessation potential of J. vahlii Roth. via murine model of neuropathic pain and its phytochemical, toxicological and antioxidant profiles. Materials and methods: The hydro-alcoholic extract of J. vahlii (HAEJv) prepared by maceration technique was subjected to preliminary phytochemical screening, total bioactive content determination, UPLC-QTOF-MS and GC-MS analysis. Toxicity assessment was carried out by using brine shrimp lethality assay and acute oral toxicity test. Murine model of neuropathic pain was applied to assess the antineuropathic potential of the species. Furthermore effect of the extract on catalase, superoxide oxide dismutase (SOD), Glutathione (GSH), interleukin-1beta (IL-1β) and total necrosis factor-alpha (TNF-α) was also studied. In vitro antioxidant profile was explored by using four methods; 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2-azinobis(3-ethylbenothiazoline)-6-sulfonic acid (ABTS), CUPric reducing antioxidant capacity (CUPRAC) and Ferric reducing antioxidant power (FRAP) assay. Results: The phytochemical screening revealed the presence of phenols, flavonoids, coumarins, alkaloids and lignans as the major classes of secondary metabolites. The extract was found rich in total phenolics content (TPC) and total flavonoids content (TFC) with identification of total 59 bioactives in UPLC-QTOF-MS and 40 compounds in GC-MS analysis. The extract was found nontoxic up to 4000 mg/kg (p.o.) in mice and no mortality observed in brine shrimp lethality assay. The HAEJv significantly reduced number of acetic acid induced abdominal constrictions at 100 mg/kg (p < 0.01) and 200 mg/kg (p < 0.001) and increased paw withdrawal threshold p < 0.05 at 100 mg/kg and p < 0.001 at 200 mg/kg, and an increase in tail withdrawal latency time p < 0.001 at 200 mg/kg was observed. The extract significantly increased levels of catalase, SOD and GSH while decreased IL-1β and TNF-α levels in sciatic nerve tissue of mice. HAEJv showed highest antioxidant activity through CUPRAC method 121.32 ± 1.22 mg trolox equivalent per gram of dry extract (mg TE/g DE) followed by DPPH 81.334 ± 4.35 mg TE/g DE, FRAP 69.89 ± 3.05 mg TE/g DE and ABTS 38.17 ± 2.12 mg TE/g DE. Conclusion: The current study back the traditional use of J. vahlii in pain cessation through antioxidant based antineuropathic pain activity and revealed the extract non-toxic with number of functional phytoconstituents and warrants further research on isolation of the compounds and sub-acute toxicity studies. Graphical abstract: Image 1 Highlights: Justicia vahlii Roth. is traditionally used in South Asia for treating toothache and skin diseases. Identification of bioactives in hydro-alcoholic extract was performed using UPLC-QTOF-MS and GC-MS analysis. The brine shrimp lethality assay and acute oral toxicity confirmed the non-toxic nature of the extract. The extract attenuated vincristine induced neuropathic pain, increased oxidative stress markers and decreased inflammatory mediators in mice. Flavonoids may be the core phytoconstituents responsible for the pharmacological effects of the extract.